Environmental Policy Evaluation in Green Village Innovation in Yogyakarta Special Region - Ambar Teguh Sulistiyani (Journal of Public Administration and Local Governance, 2018)
Green village is such an ideal dream of a settlement innovation with integrated management, fulfilling the health standard, equipped with environmental management facility and is built through social engineer movement. The starting point of green village development is government policy that proclaim Program Indonesia Hijau (Green Indonesia Movement). Minister of Environment Regulation Number 2 of 2012 has regulated programs aiming for green Indonesia. Besides, there is also Minister of Environment Regulation Number 19 of 2012 concerning climate village. In order to implement the programs aiming for green Indonesia, green village and climate village movements are needed.Community participation becomes the main point in the initiation of green village. Due to the important role of stakeholder, the synergy among actors is needed in order to create collaboration in developing green village. Considering the aspect of government policy, community active role needs to be regulated by Minister of Environment Regulation Number 17 of 2012 concerning Community Participation. Meanwhile, the realization of activities which fulfill the standard of green village is carried out through waste bank management, which is regulated by Minister of Environment Regulation Number 13 of 2012 concerning The Implementation of Reduce, Reuse and Recycle through waste bank.Some policies which are regulating from normative principle have been available in national level. Explicitly, these policies have close relationship.  These policies will be easier to be implemented if each of them has synergy, strengthen one another, and is followed by derivative policies in regional level. This paper investigates the evaluation of synergy relationship among policies and analyze the availability of derivative policies particularly in Daerah Istimewa Yogyakarta.